2003
DOI: 10.1093/milmed/168.8.639
|View full text |Cite
|
Sign up to set email alerts
|

Falciparum Malaria: An Outbreak in a Military Population on an Operational Deployment

Abstract: ARs appeared to be higher where the risk of hostile activity was higher. The evidence base concerning the use of malarial protection measures remains valid. The AR associated with deployment of a force to a high malaria risk area with a high associated risk of hostile action appears to be 0.78 cases per person-years exposure. The AR for personnel deployed to a high malaria risk area with a low risk of hostile action appears to be 0.078 cases per person-years exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Tuck et al [3], have reported an outbreak among military personnel deployed in Sierra Leone exposed to high risk of falciparum malaria. The outbreak resulted from inadequate compliance of protection policies during operational commitments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuck et al [3], have reported an outbreak among military personnel deployed in Sierra Leone exposed to high risk of falciparum malaria. The outbreak resulted from inadequate compliance of protection policies during operational commitments.…”
Section: Discussionmentioning
confidence: 99%
“…This involve intensive pre-deployment health education which incorporate the A, B, C, D approach to malaria protection [3]. A is awareness, B is bite avoidance, C is chemoprophylaxis, and D is diagnosis (early diagnosis and aggressive curative therapy).…”
Section: Discussionmentioning
confidence: 99%
“…In a UK deployment to Sierra Leone in 2000, >200 troops developed malaria 22. In 2003, in adjacent Liberia, nearly 20% of 225 deployed US Marines developed the disease; it was subsequently found that only 10% of the population at risk had been compliant with chemoprophylaxis and none had slept under mosquito nets 23.…”
Section: Vector-borne Diseasementioning
confidence: 99%
“…The health agencies have always been determined to eradicate malaria but the emergence of drug resistance, widespread resistance to available insecticides, wars, massive population movements, and lack of community participation have made the long-term maintenance of the effort untenable. Malaria episodes have been reported from the armed forces all around the world as the troops are not able to take precautions during operation and duty hours 29,30 . In malaria hyper endemic areas such as north eastern region of India, the military forces have always been at the risk of malaria infection probably due to duty demand and sometimes movement of susceptible soldiers from the non endemic zone.…”
Section: Malaria Free Cantonmentmentioning
confidence: 99%